2021
DOI: 10.1111/jfpe.13768
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling and thermodynamic properties of the drying kinetics of trapiá residues

Abstract: Trapi a (Crataeva tapia L.) is an edible, arboreal fruit species found in Brazil, of which the pulp is suitable for industrialization. The residual peel and seeds are sources of bioactive compounds and can be used after appropriate treatment. Such fruit parts have been introduced as ingredients in various applications to reduce waste in agricultural production and take advantage of the presence of nutrients, but to make them viable for industrial use, the moisture content of the product should be reduced, enab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 38 publications
1
15
0
7
Order By: Relevance
“…The effect of the drying temperature on the effective diffusivity was evaluated using an Arrhenius‐type equation, which described the relationship between the activation energy and the speed at which the reaction occurred (Moura et al., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The effect of the drying temperature on the effective diffusivity was evaluated using an Arrhenius‐type equation, which described the relationship between the activation energy and the speed at which the reaction occurred (Moura et al., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The drying constant k can be used as an approximation to characterize the temperature effect, tending to increase with it, since high temperatures lead to higher drying rates, reaching the equilibrium water content faster. An increase in the drying constant (k) was also observed with increases in drying temperature (50-80 °C) for the Midilli, Diffusion Approximation, Henderson & Pabis, and Newton models for the trapiá peel residues (Moura et al, 2021). Parameter n has a moderating effect on time and corrects the likely errors resulting from the neglect of internal resistance to water transfer (Mendonça et al, 2019).…”
Section: Resultsmentioning
confidence: 85%
“…With the calculation of the water content ratio, curves of drying kinetics were plotted, represented by the water content ratio (dimensionless) as a function of drying time (min). For the selection of the most suitable models for the description of the foam mat drying process, 10 equations were fitted to the drying data (Table 1) frequently used to represent the drying kinetics (Moura et al, 2021;Omolola et al, 2019). The non-linear regression models using the Quasi-Newton estimation method were fitted using the computer software Statistics version 7.0.…”
Section: Methodsmentioning
confidence: 99%
“…Corrêa, Oliveira, Oliveira, Botelho, and Goneli (2017) in rice drying reported a reduction in enthalpy from 48.47 to 48.13 kJ/mol between temperatures of 35 and 75°C. Moura et al (2021) observed a reduction in enthalpy from 15.50 to 15.25 kJ/mol in bark and 21.52 to 21.27 kJ/mol in trapia seed.…”
Section: Resultsmentioning
confidence: 99%
“…Increased energy of Gibbs in agricultural products is reported in the literature by , Botelho, Granella, et al (2015), Cagnin et al (2017), Oliveira, Oliveira, Resende, and Silva (2018), and Moura et al (2021 in sorghum grains, garlic, mesocarp of baru fruits, and trapiá leavings, respectively.…”
Section: Resultsmentioning
confidence: 99%